Coloration of chicks modulates costly interactions among family members. (18th April 2018) - Morales, Judith; Velando, Alberto
Abstract : Offspring in many animals display ornaments during parental dependency, but their role remains unclear. By reducing the plumage color of blue tit nestlings, we found that color influences sib-sib interactions, and also interactions between fathers (but not mothers) and chicks. Color-reduced nestlings received similar amounts of parental food, but they gained less body mass than control siblings, suggesting that ornamentation during early life plays an important role on social-mediated costs. Abstract: The resolution of family conflicts over parental care involves elaborate behavioral interactions where signals and information exchange play a central role. Usually, the focus is on offspring begging and adult signals and their effect on parental provisioning. Yet, despite offspring of many animal species display structural ornaments during parental dependency, their role in intrafamily conflicts remains practically unexplored. In the blue tit, Cyanistes caeruleus, we experimentally manipulated nestling ultraviolet (UV) color and food availability in 60 broods to investigate if family members flexibly adjust their decisions according to color under different conditions. Feeding rates were not affected by experimental treatments, but plumage color did affect parent–offspring interactions in the form of prey-testings (when a parent places a prey item into a nestling's gape but removes it again). In nonsupplemented nests, fathers but not mothers tested more prey on UV-reduced offspring, suggesting that fathers evaluate less ornamented chicks when food is scarce. As predicted by theoretical studies, UV-reduced nestlings increased begging in food-supplemented nests, although only to mothers. Moreover, UV-reduced nestlings increased parent-absent begging in all nests, indicating that plumage color affected sib-sib competitive interactions. Finally, UV-reduced offspring gained less body mass and this was probably due to costly intrafamily interactions. Overall, our results suggest that ornamentation during early life plays an important role on social-mediated costs and reveals sex-specific parental strategies according to offspring ornaments.